Religious upbringing and current religiosity in Spanish nursing and medicine students - Diaz-Moran, Sira (Mental health, religion & culture, 2013)
The influence of religious education in the family upon current spiritual and religious tendencies was assessed in a sample of 599 Spanish nurse and medicine students using a religiosity scale and answers to a series of belief/disbelief statements. Results showed that nursing and medicine students were equally low-religious, with no differences in religiosity total scores between participants coming from religious families; however, medical students coming from nonreligious families showed higher religiousness than the corresponding nursing trainees. This distinction appeared both across religiosity items and in a variety of responses to belief/disbelief of Christian/secular assertions. Regression analysis showed that religious family background was a consistent predictor of religious beliefs at young adulthood, and its influence was higher for medical students. In addition to establish religious upbringing as an important factor modulating enduring religiosity, these findings provide distinctions between nurse and medical trainees, and reproduce, in a Spanish mainly catholic sample, the structure of religiosity factors previously found on North American mainline protestants.